2010
DOI: 10.1182/blood-2009-12-258038
|View full text |Cite
|
Sign up to set email alerts
|

PGE2 transiently enhances DC expression of CCR7 but inhibits the ability of DCs to produce CCL19 and attract naive T cells

Abstract: Prostaglandin E 2 (PGE 2 ) is an inflammatory mediator often used to increase CCR7 expression in the dendritic cells (DCs) used as cancer vaccines and to enhance their responsiveness to lymph nodeassociated chemokines. Here, we show that high surface expression of CCR7 on PGE 2 -matured DCs is associated with their suppressed production of the endogenous CCR7 ligand, CCL19, and is reversible by exogenous CCL19. In contrast to the PGE 2 -matured DCs, DCs matured in the presence of toll-like receptor (TLR) ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 37 publications
4
79
2
Order By: Relevance
“…Similarly, PGE 2 inhibits secretion of IFNα by Toll-like receptor (TLR)-activated PDCs via EP2/4, which results in reduction of Th1 cytokine secretion and induction of Th2 cytokine secretion by T cells (Fabricius et al, 2010). PGE 2 also inhibits the ability of DCs to produce CCL19 that attracts CCR7-expressing naïve CD4 + T cells (Muthuswamy et al, 2010). More interestingly, PGE 2 has been recently showed to redirect the differentiation of human DCs into monocytic MDSCs (Obermajer et al, 2011a).…”
Section: Pge2 and Immune Cellsmentioning
confidence: 99%
“…Similarly, PGE 2 inhibits secretion of IFNα by Toll-like receptor (TLR)-activated PDCs via EP2/4, which results in reduction of Th1 cytokine secretion and induction of Th2 cytokine secretion by T cells (Fabricius et al, 2010). PGE 2 also inhibits the ability of DCs to produce CCL19 that attracts CCR7-expressing naïve CD4 + T cells (Muthuswamy et al, 2010). More interestingly, PGE 2 has been recently showed to redirect the differentiation of human DCs into monocytic MDSCs (Obermajer et al, 2011a).…”
Section: Pge2 and Immune Cellsmentioning
confidence: 99%
“…PGE2-treated DCs migrate more deeply into the center of the lymph nodes to the sites of T-cell priming in the mice [56]. However, clinical studies comparing the in vivo migratory capacity of differentially matured human DCs did not reveal any migratory advantage of DCs conferred by exogenous PGE2 [54,57]. A recent study in PGES-1-deficient murine model exhibited an abrogation of PGE2 synthesis by DCs and their altered cytokine profile, but it did not reveal any impact on their maturation status or migratory function [58], which indicated that DC maturation and effective lymph node migration could occur in the absence of PGE2.…”
Section: Effect Of Pge2 On DC Migration and Maturationmentioning
confidence: 86%
“…And the signaling mechanisms involved in PGE2-induced MMP-9 expression in DCs are mediated through the EP2/EP4-cAMP-PKA/PI3K-ERK signaling pathway [53]. However, recent data demonstrated that PGE2 transiently enhances DC expression of CCR7 but inhibits the ability of DCs to produce CCL19 and attracts naïve T cells and are rapidly compensated after DC removal from the CCL19 rich maturation environment [54]. Furthermore, the balance between MMP and tissue inhibitors of metalloproteinases (TIMP) has been shown to modulate DC migration.…”
Section: Effect Of Pge2 On DC Migration and Maturationmentioning
confidence: 94%
“…We have previously shown that HK and gut CD8α + cells express CCR7 (29) indicating that the source of cells used in our studies should not be reason why chemotaxis results were negative. Some reports have shown the importance of PGE2 on the migratory ability of CCL19 in mammalian monocytes (8386). Thus, we also pre-activated HKLs with PGE2 but still failed to observe any chemotactic effects in vitro .…”
Section: Discussionmentioning
confidence: 99%